Identity Negotiation and Intercultural Adaptation through Hidden Curriculum at Islamic Higher Education - Ariyani, Nili; Sapuadi (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines identity negotiation and intercultural adaptation among Dayak and non-Dayak students in a multicultural higher education context, with a particular focus on the role of hidden curriculum in shaping intercultural experiences. While existing studies in intercultural communication have predominantly emphasized formal curriculum and institutional frameworks, limited attention has been given to the role of informal social interactions as a mechanism for developing intercultural competence. Addressing this gap, this study investigates how the hidden curriculum mediates identity negotiation and intercultural adaptation in everyday campus interactions. This study employed a mixed-methods approach, integrating quantitative data collected via a Likert-scale questionnaire administered to 30 students with qualitative data from in-depth interviews. The findings indicate that students demonstrate a generally positive tendency in managing and expressing their cultural identities, while also showing the ability to adapt to culturally diverse environments. More importantly, the study reveals that hidden curriculum functions as a key mechanism through which intercultural values such as tolerance, cooperation, and mutual respect are internalized through daily social interactions. Theoretically, this study contributes to the global intercultural communication literature by positioning hidden curriculum as an integrative dimension that connects identity negotiation and intercultural adaptation. It highlights that intercultural competence is not solely developed through formal educational structures, but is significantly shaped by informal, context-dependent social processes. Practically, the findings provide implications for Islamic higher education institutions in designing communication approaches and curricula that are dialogic, inclusive, and culturally responsive. This study thus offers both contextual insight from an Indonesian multicultural setting and broader theoretical implications for understanding intercultural dynamics in higher education.